Early afforestation influences on soil fungal communities but bacterial and oomycetes are slower to respond - Nicola M. Reid; Preeti Panda; Sarah L. Addison; Rebecca L. McDougal; Loretta G. Garrett; Thomas S.H. Paul; Steve A. Wakelin (Applied Soil Ecology, 2026)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Unravelling Changes in the Pinus radiata Root and Soil Microbiomes as a Function of Aridity - Sarah L. Addison; Zhen‐Zhen Yan; Tom Carlin; Megan A. Rúa; Simeon J. Smaill; Kaitlyn Daley; Brajesh K. Singh; Steve A. Wakelin (Global Change Biology, 2025)
Increased aridity is emerging as a key impact of climate change in terrestrial ecosystems globally. Forest biomes are particularly vulnerable to the impacts of changing environmental conditions due to their long‐lived and sessile nature. Microbiomes have coevolved with plants under changing environmental conditions with shared fitness outcomes. However, both the movement of plants via domestication and rapid pace of environmental change may impact the ability of plants to recruit microbial symbionts that support environmental stress tolerance. This study investigates the effects of aridity on tree‐root microbiome symbiosis, focusing on the widely planted Pinus radiata . By sampling a broad geographic range and diverse environmental gradients, we reveal how aridity, soil and climatic variables shape microbial communities in P. radiata roots and soils. Our findings highlight that while aridity significantly predicts microbial community assembly, other environmental variables such as soil pH and organic carbon, strongly influence bacterial diversity. Groups of both bacterial and fungal taxa were identified as conditionally present with aridity, underscoring their importance in P. radiata resilience under increasingly environmental stress. Based on the transition of current mesic ecosystems to arid conditions under climate change, we found these arid associated taxa vary in their frequency in bulk soils projected to become arid. These results highlight the risk that these taxa will need to be recruited by other means. Ecological filtering by the host and environmental conditions fosters a “friends with benefits” relationship, wherein certain microbial taxa provide key benefits, such as extension of phenotypic tolerance to water limitation, to the host. Both bacterial and fungal communities are shaped more by stochastic than deterministic assembly processes, suggesting a complex interplay of host and environmental factors in community structure formation. The insights gained have implications for understanding the resilience of tree species and the ecosystem services they provide under future climate scenarios.

Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.